Theoretical investigation of excitonic magnetism in LaSrCoO4. (6th March 2018) - Fernández Afonso, J; Sotnikov, A; Kuneš, J
Abstract: We use the LDA+U approach to search for possible ordered ground states of LaSrCoO4 . We find a staggered arrangement of magnetic multipoles to be stable over a broad range of Co 3 d interaction parameters. This ordered state can be described as a spin-density-wave-type condensate of d x y ⊗ d x 2 − y 2 excitons carrying spin S   =  1. Further, we construct an effective strong-coupling model, calculate the exciton dispersion and investigate closing of the exciton gap, which marks the exciton condensation instability. Comparing the layered LaSrCoO4 with its pseudo cubic analog LaCoO3, we find that for the same interaction parameters the excitonic gap is smaller (possibly vanishing) in the layered cobaltite.